An Observational Study On Medo Roga (Sthaulya) – A Most Prevalent Lifestyle Disorder In India In The Present Era (Journal of Pharmaceutical Negative Results, 2023)
One of the non-communicable diseases is obesity. In biomedical research, the etiopathogenesis, treatment, and effects of obesity are not fully understood and are continually developing. It is a multifactorial metabolic illness, and in Ayurveda, it is comparable to Sthaulyata or Medoroga. Jatharagni and Dhatwagni, in particular, Medodhatwagni, are vitiated by this illness. Dhatuparinama is impacted as a result, causing Medo Dhatu to develop improperly. Ama Dosha interacts with numerous Dhatus and forms at various levels. Simply put, Medodhatwagnimandyata results in excessive production of Sama Meda Dhatu, which in turn produces the Medo Roga. This Sama Meda builds up in the body and accumulates in different Srotases, which causes srotorodha and other issues. Sthaulya and the name Medo roga may be associated based on their clinical symptoms. The fourth Dhatu of the body, known as Medodhatu (Medas), is ubiquitous. It is mostly seen as a thick layer inside the udara (Abdomen), linked to its kalas, beneath the twak (Skin). The mula of this system is referred to as the Vrikka and Vapavahan. Slight obesity, also known as sthaulya, is when a person's weight or body size increases significantly owing to the buildup of extra fat. This condition is frequent in people over the age of 40, in women who have just given birth, and in women going through menopause. Overeating and faulty hormonal function are both attributable to disturbed appetite control mechanisms in the body, which cause excessive fat accumulation.